(untitled) (Indian Journal of Physiotherapy and Occupational Therapy - An International Journal, 2020)
Background: Low back pain is a common musculoskeletal disorder which may be acute, sub acute and chronic in nature. Low back pain is expressed in 42% in adults. Low back pain occurrence is at an early age and can cause disease progression. Low back pain is due to suboptimal breathing patterns and impairments of posture and trunk stability. Many muscles used for the postural control and respiration are same that is diaphragm, transverses abdominis and muscles comprising the pelvic floor. The diaphragm is the key muscle for the respiratory pump with attachment from the lower six ribs, xiphoid process of sternum and the vertebral column. Diaphragm performs both postural and breathing function. Disruption in one function could negatively affect the other. Objectives: 1.To find the Effectiveness of 90/90 bridge with ball and balloon exercises and Interferential therapy for pain and disability in low back pain among young adults. 2. To find the Effectiveness of Interferential therapy for disability and pain in low back pain among young adults. 3. To compare the effectiveness of 90/90 bridge with ball and balloon exercise and Interferential therapy together and Interferential therapy alone for pain and disability in back pain among young adults. Study Design: A quasi experimental study Methods: 18 adults who had mechanical low back pain were included in the study. Participants were divided into 2 groups .Group A received 90/90 bridging with ball and balloon and interferential therapy and Group B received interferential therapy alone. Exercises were given twice a day for 3 days for 4 weeks. Pre and post exercise evaluation is taken by using numerical pain rating scale and Modified Oswestry disability index scale Questionnaire. Data was analyzed using independent T test and paired T test. Result: In both the group there was improvement but there is a significant difference in 90/90 bridge with ball and balloon exercise and interferential therapy than the IFT alone among the young adults with low back pain. Conclusion: This study concludes that there is greater effect of 90/90 bridge with ball and balloon exercise on patients with mechanical low back pain.